Identifying the default: The Ottoman empire and the İstanbul bourse in the nineteenth century - Avni Önder Hanedar; Talat Ulussever; Murat Ertuğrul (Turkish Economic Association, 2018)
This paper tests how default of a government is reflected in a bond market prior to its declaration to the public. There was an unsettled discussion on that the Ottoman moratorium was not surprise. The price of the General debt bond traded at the çIstanbul bourse of the Ottoman Empire between 1874 and 1883 is manually collected. To identify the default risk of the Ottoman state, the paper analyses volatility jumps in return of the bond, using the ICSS and SWARCH methodology. Our results indicate higher volatility with decreasing price before the official declaration of the moratorium. This corresponds to increasing intensity of the rebellions in the Ottoman Empire, implying higher budget deficits and risks on the redemption of debts. The findings suggest the presence of a leading event for the default, as it can be seen that by the default announcement in October 1875 the bond price displays a significant and continuous decrease. This supports the lack of the dissemination of news on the moratorium prior to the declaration.
Keywords: 330; The moratorium of the Ottoman state; the İstanbul bourse; Structural breaks; the ICSS test; SWARCH